Aging, Retirement and Pay-As-You-Go Pensions - Giam Pietro Cipriani (Institute for the Study of Labor (IZA), 2016)
In this paper we consider the effects of population aging on a pay-as-you-go financed defined contributions pension scheme. We show that when retirement decisions are endogenous, aging increases the retirement age and the steady state level of capital. The effect on pension payouts is in general ambiguous, except for the solution of full retirement, when this effect is unambiguously negative.
Keywords: J13; H55; 330; retirement; aging; PAYG pensions; overlapping generations model